Designing for the digital age : how to create human-centered products and services. - Goodwin, Kim, ....- (Indianapolis : Wiley, 2009)
1 Goal-Directed Product and Service Design. 2 Assembling the Team. 3 Project Planning. 4 Research Fundamentals. 5 Understanding the Business. 6 Planning User Research. 7 Understanding Potential Users and Customers. 8 Example Interview. 9 Other Sources of Information and Inspiration. 10 Making Sense of Your Data: Modeling. 11 Personas. 12 Defining Requirements. 13 Putting It All Together: The User and Domain Analysis. 14 Framework Definition: Visualizing Solutions. 15 Principles and Patterns for Framework Design. 16 Designing the Form Factor and Interaction Framework. 17 Principles and Patterns in Design Language. 18 Developing the Design Language. 19 Communicating the Framework and Design Language. 20 Detailed Design: Making Your Ideas Real. 21 Detailed Design Principles and Patterns. 22 Detailed Design Process and Practices. 23 Evaluating Your Design. 24 Communicating Detailed Design. 25 Supporting Implementation and Launch. 26 Improving Design Capabilities in Individuals and Organizations.